Using games in the young learner english classroom in Transcarpathia - Nagy-Kolozsvári Enikő; Надь-Коложварі Еніке; Fábián Márta; Фабіян Марта; Huszti Ilona; Густі Ілона (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. The study was conducted in one of the regions of a war-torn country, Ukraine. The region is Transcarpathia, which is the westernmost territory of the country bordering Hungary, Slovakia and Romania. The research was carried out in January, 2023. Children study mainly English as a foreign language. The number of weekly hours is presented in Table 1 (Huszti 2020). There were daily air raid alarms in the region because of the war that had been going on in the country since 24 February, 2022. According to the safety regulations, children have to leave their classrooms with their teachers and go to the bomb shelter of the school the moment they hear the sirens, and stay there until the alarm is off. Sometimes it means an hour, at other times it can last two or three hours (Huszti, Bárány, Lechner, & Fábián 2023). If the children are lucky, there is internet access in the shelter and they can use their digital devices for learning purposes. However, if there is a power shortage, the internet is not available, so then it is the time for applying traditional games for language learning that do not require electricity.
Keywords: games; Transcarpathia; gamification